The great buildings collection - Matthews, Kevin 1959- (Artifice, 1994)
Provides a wealth of information on many of the most famous buildings in the world, along with other types of dwellings. Includes historical information, photos, architectural details and plans, architect information, books on architecture, 3D walkthrough computer models, picture index, discussion group, search engines, and access to ArchitectureWeek electronic magazine.